Subjective sleep quality in adolescent girls with menstrual disorders - S. E. Bolshakova; I. M. Madaeva; O. N. Berdina; E. E. Khramova; O. V. Bugun; L. V. Rychkova (Acta Biomedica Scientifica, 2024)
Background. Menstrual irregularities occupy a leading place among gynecological diseases in girls. It is assumed that there is a connection between reproductive system disorders and sleep in adolescent girls, but to date this issue remains poorly understood.The aim. To study the subjective sleep quality of adolescent girls with irregular and regular menstrual cycles.Materials and methods. A survey of 461 teenage girls living in the city of Irkutsk and the Irkutsk region was conducted in the period from January 2023 to May 2024. Two groups were formed: group 1 – teenage girls with an irregular menstrual cycle (n = 121), group 2 – teenage girls without menstrual disorders (n = 340).Results. Adolescent girls with irregular menstrual cycles had sleep disturbances more often and longer, falling asleep later and taking longer, waking up later, poor sleep and daytime sleepiness. The average duration of sleep on weekdays, regardless of the nature of the menstrual cycle, was below the normal values for this age, which indicates a sleep deficit in adolescent girls.Conclusions. Poor sleep hygiene in adolescent girls, poor quality and short sleep cause disruption of the circadian rhythm that regulates the menstrual cycle. Increasing the duration and improving the quality of sleep are an important component of the formation and maintenance of reproductive health in adolescent girls. Further research is needed to better understand the complex relationships between circadian sleep-wake rhythms and the reproductive system in adolescent girls.